Implementation of a Lock In Amplifier for Optical Spectroscopy Measurements - Homs, R.; Purón, E. (Revista Cubana de Física; Vol 31 No 1 (2014), 2014)
The experimental set-up of an optical spectroscopy measurement based on virtual instrumentation is presented. A lock-in amplifier has been implemented by applying digital signal processing techniques to a PC-based data acquisition board. The application was developed in C++, on top of open source Qt/Qwt graphical framework. The spectral emission of reference light sources were measured in order to calibrate and validate the system.